Apakah Implementasi “Reinventing Policy” Meningkatkan Tax Compliance” Pajak Badan? - Rinaldi Munaf; Nini Syofriyeni; Yurniwati Yurniwati (Universitas Andalas, 2019)
This research is aims to analyze and describe the level of compliance of corporate taxpayers after the Reinventing Policy is implemented. The study was conducted on the Agency taxpayers in the Padang KPP office. The data was collected using a questionnaire. The analytical method used is descriptive statistics, which evaluates the level of achievement of respondents' answers that reflect the level of tax compliance and implementation of Reinventing Policy and linear regression analysis to determine the effect of Reinventing Policy on corporate taxpayer compliance. The results of descriptive statistical research indicate the Reinventing Policy variable has a level of achievement of respondents' answers of 3.78 which means that the implementation of Reinventing Policy is quite good. This was followed by the level of compliance of corporate taxpayers which was also quite good as indicated by the level of achievement of respondents' answers of 3.94. The results also showed that the Reinventing Policy had a significant effect on corporate taxpayer compliance. This finding implies that the policies have been responded by taxpayers by showing changes in their behavior.